A brief review of the crucial progress on heterometallic polyoxotungstates in the past decade. Issue 6 (22nd January 2016) - Liu, Jiancai; Han, Qing; Chen, Lijuan; Zhao, Junwei
Abstract : In this article, the main progress on heterometallic polyoxotungstates in the past decade involving syntheses, structures and related properties is highlighted and discussed. Abstract : Heterometallic polyoxotungstates (HMPOTs) are still a challenging and attractive materials in polyoxometalate chemistry despite having generated remarkable interest in recent years not only on account of a variety of new structures and topologies but also because of their multiple potential applications in catalysis, magnetism, nanoscience, electrochemistry and photochemistry. This brief highlight article is principally focused on an overview of four types of HMPOTs: polyoxotungstate-based main-group (MG) and transition-metal (TM) heterometallic derivatives (PMGTMHDs), polyoxotungstate-based TM and TM heterometallic derivatives (PTMTMHDs), polyoxotungstate-based rare-earth (RE) and TM heterometallic derivatives (PRETMHDs) and polyoxotungstate-based RE and RE heterometallic derivatives (PREREHDs), and gives a summary of some representative examples involving their syntheses, structures and related properties. In addition, an outlook on these materials is also provided.